Managing sports mega-events: key stakeholders - Kozak, Marek W. (Journal of Public Governance, 2017)
Sports mega-events which belong solely to the FIFA, UEFA or IOC have recently become a field of interest for many stakeholders: the rights owners (Organization), administration, and business (media in particular). The main aim of this paper is an analysis of sports mega-event management schemes and practices, and the key thesis is that the system is mostly profit-oriented. Profit and cost is similarly important, as event mechanisms, based first of all on financial agreements of central administration and the UEFA, that is the main, but not the only, stakeholders. Event mechanisms determine profits. This paper explores the gap in our knowledge about the mechanism of sports mega events, which is well visible in literature review. Due to the 2014 war in Eastern Ukraine, only the Polish side was analyzed.